Determinants of Noneconomic Damages in Medical Malpractice Settlements and Litigations: Evidence from Texas since 1988 - Jun Zhou (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2010)
There have long been claims that compensations for noneconomic damages are random because tort law does not provide clear guidance regarding these compensations. I investigate, in both settled and tried medical malpractice cases, whether noneconomic damage payments are arbitrary and what determines the probability and size of these payments. I find that payments for noneconomic damages are not completely random. They vary, in predictable ways, with observable characteristics of the case. The data suggest similar patterns in non-medical malpractice cases. I end by discussing the implications of my findings for the debate on the efficiency and rationale of noneconomic damage compensation.
urn:nbn:de:bvb:19-epub-13206-4
Keywords: K13; K32; K41; 330; Haftung; Medizin; Schiedsgerichtsbarkeit; Zivilprozess; Kompensationsmaßnahme; Texas